Cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry and preparation method thereof

By using cellulose nanocrystalline composite polyacrylate emulsion copolymer slurry, the problems of complex slurry adjustment process, high sizing rate and environmental pollution during sizing of high-branch polyester cotton blended yarns are solved, and the slurry performance is improved and the slurry is reduced, and the slurry is easily biodegradable.

CN119877278APending Publication Date: 2025-04-25QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311377832.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When sizing high-branch polyester cotton blended yarns, the slurry adjustment process is complex, the slurry rate is high, and a large amount of PVA-type slurry that is difficult to biodegrade is used, resulting in environmental pollution.

Method used

Cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry is used, which consists of polyacrylate emulsion copolymerization slurry and cellulose nanocrystal aqueous dispersion. The mass amount of cellulose nanocrystals accounts for 0.5%-2.5% of the solid content of the polyacrylate emulsion copolymerization slurry. By dehydration and concentration under reduced pressure, a slurry with a solid content of less than or equal to 45%.

Benefits of technology

The slurry is easy to biodegradate, simplifies the slurry operation, reduces the slurry rate, and significantly improves the comprehensive weaving properties of the slurry, which can replace industrial formula R for 45s polyester-cotton blended yarn sizing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry and a preparation method thereof, and the preparation method is characterized by comprising the following steps: adding polyacrylate emulsion copolymerization slurry into a cellulose nanocrystal aqueous dispersion, then fully and uniformly stirring to obtain a mixture, and then adding the polyacrylate emulsion copolymerization slurry into the cellulose nanocrystal aqueous dispersion to obtain the cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry. The preparation method comprises the following steps: preparing cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry with the solid content of less than 30%, and carrying out reduced pressure dehydration concentration on the obtained cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry to obtain cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry with the solid content of less than or equal to 45%. When the cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry provided by the invention is used for sizing 45s polyester-cotton blended yarns, the ubiquitous defects in the prior art that the size mixing process is complicated, the sizing rate is high, and a large amount of PVA (Polyvinyl Alcohol) slurry which is difficult to biodegrade and pollutes the environment is used can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a textile pulp and a preparation method thereof, in particular to an eco-friendly cellulose nano-crystal composite polyacrylate emulsion copolymer pulp and a preparation method thereof. Background Art

[0002] As we all know, textile sizing agents are mainly divided into three categories: starch, polyvinyl alcohol (PVA) and polyacrylic acid. Among them, polyvinyl alcohol (PVA) is widely used as the main sizing agent for cotton, polyester-cotton, polyester-viscose, nylon and other yarns due to its excellent film-forming properties, adhesion and good compatibility with other sizing agents, and is considered to be an ideal sizing agent. However, with the strengthening of environmental protection awareness, developed countries, especially European countries, have banned the use of PVA as a textile sizing agent due to the shortcomings of PVA sizing agents being difficult to biodegrade and causing serious pollution to the environment. my country has also proposed the development goal of not using or using less PVA sizing agents in the sizing process.

[0003] Due to its excellent wearing performance, the demand and output of high-count polyester-cotton blended fabrics have been continuously increased, and they have occupied a large proportion in cloth production. However, due to the strong hydrophobicity and smooth surface, it is relatively difficult to size pure polyester or polyester-cotton blended yarns. In order to meet the weaving performance, for yarn counts of 45 s For high-count polyester-cotton yarns of 1000 and above, the warp sizing still needs to use a relatively high proportion of PVA sizing agent, and the sizing rate is usually ≥13%, which leads to the disadvantages of the existing sizing process, such as complex sizing process, high sizing rate, and especially the large use of PVA sizing agents that are difficult to biodegrade and cause environmental pollution. In order to avoid the pollution of the environment caused by PVA sizing agent, simplify the sizing process, and reduce the amount of sizing agent, it is urgent to develop a new type of textile sizing agent with excellent sizing performance, low sizing rate, and easy treatment of desizing wastewater, so as to realize the development strategy of green energy conservation and emission reduction of my country's textile industry.

[0004] From the perspective of resin structure, polyacrylic acid slurry is classified into three structural types: pure acrylic acid, acrylic acid ester and styrene acrylic acid. From the perspective of dosage form, polyacrylic acid slurry includes three dosage forms: aqueous solution type, water emulsion type and solid powder type. It is a polyacrylic acid textile slurry prepared by free radical or ionic polymerization of one or more mixed monomers composed of acrylic monomers such as acrylic acid or methacrylic acid, acrylate or methacrylate, acrylamide and acrylonitrile and vinyl monomers such as vinyl acetate and styrene. Due to the designability of its structure and performance, it can meet the sizing performance requirements of different yarns. At the same time, this type of slurry in the desizing wastewater is easy to flocculate, recover and be biodegraded, so it is considered to be an eco-friendly textile slurry. However, compared with PVA slurry and starch slurry, the production cost of this type of slurry is relatively high, so it is currently widely used as an auxiliary slurry for sizing various types of yarns. Therefore, if its sizing performance can be improved and its sizing cost can be reduced by reducing the sizing rate, this type of sizing agent can be used as the main sizing agent in sizing high-count polyester-cotton blended yarns with relatively high sizing costs.

[0005] Nanocellulose is a nanoscale fiber or crystal extracted from natural cellulose. It has the advantages of being degradable, renewable, non-toxic and high-strength. It can be used to prepare various advanced functional materials with high added value. According to the different preparation methods and sources, nanocellulose can be divided into three categories: cellulose nanocrystals (CNC), cellulose nanofibers (CNF) and bacterial cellulose (BC). These three types of nanocellulose have certain differences in structure, performance and application. Among them, CNC is a nanorod-like material with natural chirality, mainly composed of crystalline regions and quasi-crystalline regions, with a diameter between 5-30nm, a length ranging from 100 nm to several microns, and an aspect ratio usually between 5-50. There is no bending, winding, bifurcation or mesh structure; CNF is mainly composed of crystalline regions, quasi-crystalline regions and amorphous regions, with a diameter of about 3-100nm, a length of up to hundreds of microns, and an aspect ratio generally greater than 10. There may be filaments, winding or mesh structures; BC is a natural nanostructured polymer material with biodegradability produced by bacteria. Existing studies have shown that the use of nanocellulose to modify polymer materials can significantly improve the mechanical properties of polymer materials. However, through literature search, so far, no research reports on the use of cellulose nanocrystals to modify polyacrylate emulsion copolymer slurry have been found. Summary of the invention

[0006] The purpose of the present invention is to provide a cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry, and the cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry provided by the present invention is used to sSizing of polyester-cotton blended yarn (polyester-cotton blending ratio is 65:35) can overcome the shortcomings of the prior art, such as complex sizing process, high sizing rate, and large amount of PVA sizing agent which is difficult to biodegrade and causes environmental pollution.

[0007] A cellulose nanocrystal composite polyacrylate emulsion copolymer slurry, characterized in that the slurry is composed of polyacrylate emulsion copolymer slurry and cellulose nanocrystal aqueous dispersion, wherein the mass amount of cellulose nanocrystals accounts for 0.5%-2.5% of the solid content (solid mass percentage content) of the polyacrylate emulsion copolymer slurry; the cellulose nanocrystals are prepared by using microcrystalline cellulose as raw material through sulfuric acid acid hydrolysis process, and the fiber length tested by atomic force microscope is 80nm-250nm and the height is 5nm-9nm; the solid content of the polyacrylate emulsion copolymer slurry is 3 0%-50%, is prepared by conventional emulsion copolymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate using water as solvent, wherein the mass percentage of acrylic acid to the total mass percentage of the mixed monomer is 2%-5%, the mass percentage of acrylamide to the total mass percentage of the mixed monomer is 15%-25%, the mass percentage of butyl acrylate to the total mass percentage of the mixed monomer is 20%-40%, the mass percentage of methyl methacrylate to the total mass percentage of the mixed monomer is 20%-40%, and the mass percentage of each monomer in the mixed monomer is 100%.

[0008] A method for preparing a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry is characterized by being implemented according to the following steps: adding polyacrylate emulsion copolymer slurry to a cellulose nanocrystal aqueous dispersion, and then fully stirring to obtain a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than 30%, and decompressing and dehydrating the obtained cellulose nanocrystal composite polyacrylate emulsion copolymer slurry to obtain a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than or equal to 45%.

[0009] The cellulose nanocrystal composite polyacrylate emulsion copolymer slurry provided by the present invention is easy to biodegrade, which can overcome the current domestic and foreign textile enterprises in 45 s The environmental pollution problem caused by the large amount of PVA sizing agent used in the sizing process of polyester-cotton blended yarn (polyester-cotton blending ratio is 65:35) is solved. The sizing agent is simple to prepare. Under the premise of significantly reducing the sizing rate, the sizing agent is used to treat 45 s The polyester-cotton blended yarn (polyester-cotton blending ratio is 65:35) is sized, and the comprehensive weaving performance of the sized yarn is significantly better than that of the combined sizing materials commonly used in the current textile industry.

[0010] The embodiments of the present invention are further described below by way of examples.

[0011] Example 1: Preparation of Cellulose Nanocrystal Composite Polyacrylate Emulsion Copolymer Slurry A Weigh 40 grams of 1% cellulose nanocrystal aqueous dispersion, add 100 grams of polyacrylate emulsion copolymer slurry PA-1 with a solid content of 40% (prepared by conventional emulsion polymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 5:20:40:35), and stir at room temperature for 1 hour to obtain cellulose nanocrystal composite polyacrylate emulsion copolymer slurry A with a solid content of 28.86%. The slurry is dehydrated under reduced pressure, and after dehydrating 50.22 grams of water, cellulose nanocrystal composite polyacrylate emulsion copolymer slurry A with a solid content of 45% can be obtained, referred to as slurry A.

[0012] Example 2: Preparation of Cellulose Nanocrystal Composite Polyacrylate Emulsion Copolymer Slurry B Weigh 66.67 g of 1.5% cellulose nanocrystal aqueous dispersion, add 100 g of polyacrylate emulsion copolymer slurry PA-1 with a solid content of 40% (prepared by conventional emulsion polymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 5:20:40:35), and stir at room temperature for 1 hour to obtain cellulose nanocrystal composite polyacrylate emulsion copolymer slurry B with a solid content of 24.6%. The slurry is dehydrated under reduced pressure, and after dehydrating 64.17 g of water, cellulose nanocrystal composite polyacrylate emulsion copolymer slurry B with a solid content of 40% can be obtained, referred to as slurry B.

[0013] Example 3: Preparation of Cellulose Nanocrystal Composite Polyacrylate Emulsion Copolymer Slurry C Weigh 40g of 1.5% cellulose nanocrystal aqueous dispersion, add 100g of polyacrylate emulsion copolymer slurry PA-2 with a solid content of 40% (prepared by conventional emulsion polymerization of a mixed monomer consisting of acrylic acid, acrylamide, butyl acrylate and methyl methacrylate in a mass ratio of 4:20:36:40), and stir at room temperature for 1 hour to obtain cellulose nanocrystal / pure acrylic polyacrylate emulsion nanocomposite slurry C with a solid content of 29%. The slurry is dehydrated under reduced pressure, and after dehydrating 38.5g of water, a cellulose nanocrystal composite polyacrylate emulsion copolymer slurry C with a solid content of 40% is obtained, referred to as slurry C.

[0014] Example 4: Sizing Experiment 1. Slurry preparation: (1) Preparation of sizing solution for actual factory sizing production: In a 2-liter beaker, add 577.8 grams of deionized water, then add 37.5 grams of PVA-1799, 5 grams of PVA-205, 50 grams of GM8-60 and 3 grams of wax flakes to prepare a sizing solution with a solid content of 13%. Start stirring and heat to 95°C. Continue stirring and keep warm for 1 hour before using for sizing. Define this sizing solution as sizing solution formula R.

[0015] (2) Preparation of cellulose nanocrystal composite polyacrylate emulsion copolymer slurry: In a 2-liter beaker, add 200 grams of cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of 40%, add 800 grams of deionized water, prepare a slurry with a solid content of 8%, start stirring, and heat to 95°C for sizing. Among them, the slurries prepared using slurry A, slurry B and slurry C are defined as slurry formula A, slurry formula B and slurry formula C, respectively. 2. Sizing process: The above-prepared sizing solution was slurried by Y606S single yarn sizing machine at 95℃ with a sizing speed of 50 m / min and a sizing pressure of 15KN on 45 s The polyester-cotton blended yarn (polyester-cotton blend ratio is 65:35) is sized.

[0016] 3. Sizing performance test According to GB / T3916-1997, the tensile breaking strength of textile single yarn, the tensile breaking strength (TS) and tensile breaking length (BL) of the sized yarn were tested, and the strengthening rate (TSR) and breaking reduction rate (BLR) of the sized yarn were calculated. According to FZ / T01058-1999, the abrasion resistance (ART) of the sized yarn was tested by the reciprocating roller method, and the abrasion increase rate (ARR) of the sized yarn was calculated. According to FZ / T01089-2000, the number of hairiness of the sized yarn was tested by the projection technology method, and the hairiness flatness rate (FDR) was calculated. According to GB / T9995-1997, the moisture regain (MRR) of the sized yarn was tested, and according to the literature [Yu Yongjun, Effect of sizing formula on loom efficiency and desizing rate of polyester-cotton varieties, Cotton Textile Technology, 2020, 48(08), 11-13], the sizing rate (SR) and desizing rate (DSR) of the sized yarn were tested. The test results of sizing performance are shown in Table 1.

[0017] Table 1 45 s Sizing properties of polyester-cotton blended yarn (polyester-cotton blend ratio 65:35).

[0018] From the data in Table 1, it can be seen that the use of cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry for 45 sThe polyester-cotton blended yarn (polyester-cotton blending ratio of 65:35) was sizing. When the sizing rate was at least 3% lower than the industrial formula, the various properties of the sizing yarns with sizing formula A, sizing formula B and sizing formula C were better than those of the industrial formula R. The results show that the use of a single cellulose nanocrystal composite polyacrylate emulsion copolymer sizing agent for sizing high-count polyester-cotton yarn can not only simplify the sizing operation and reduce the sizing rate, but also improve the sizing performance. Therefore, it can completely replace the industrial formula R for 45 s Used for sizing polyester-cotton blended yarn (polyester-cotton blend ratio is 65:35).

[0019] The above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.

Claims

1. A cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry, characterized in that The slurry is composed of polyacrylate emulsion copolymer slurry and cellulose nanocrystal aqueous dispersion, wherein the mass amount of cellulose nanocrystals accounts for 0.5%-2.5% of the solid content (solid mass percentage content) of the polyacrylate emulsion copolymer slurry; the cellulose nanocrystals are prepared by using microcrystalline cellulose as raw material through sulfuric acid acid hydrolysis process, and the fiber length tested by atomic force microscope is 80nm-250nm and the height is 5nm-9nm; the solid content of the polyacrylate emulsion copolymer slurry is 30%-50%, and it is composed of acrylic acid, The mixed monomer composed of acrylamide, butyl acrylate and methyl methacrylate is prepared by conventional emulsion copolymerization using water as solvent, wherein the mass percentage of acrylic acid to the total mass percentage of the mixed monomer is 2%-5%, the mass percentage of acrylamide to the total mass percentage of the mixed monomer is 15%-25%, the mass percentage of butyl acrylate to the total mass percentage of the mixed monomer is 20%-40%, the mass percentage of methyl methacrylate to the total mass percentage of the mixed monomer is 20%-40%, and the mass percentage of each monomer in the mixed monomer totals 100%.

2. The method for preparing the cellulose nanocrystal composite polyacrylate emulsion copolymerization slurry according to claim 1, characterized in that The following steps are implemented: adding polyacrylate emulsion copolymer slurry to cellulose nanocrystal aqueous dispersion, and then stirring the mixture thoroughly to obtain cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than 30%, and decompressing and dehydrating the obtained cellulose nanocrystal composite polyacrylate emulsion copolymer slurry to obtain cellulose nanocrystal composite polyacrylate emulsion copolymer slurry with a solid content of less than or equal to 45%.